1996
DOI: 10.1007/bf00212683
|View full text |Cite
|
Sign up to set email alerts
|

Ionic imbalance as a source of toxicity in an estuarine effluent

Abstract: A toxicity identification evaluation (TIE) was conducted on the effluent from a petrochemical plant which discharges into an estuary. The effluent had been consistently toxic to mysid shrimp (Mysidopsis bahia) but not toxic to sheepshead minnows (Cyprinodon variegatus). Phase I effluent toxicity characterization tests revealed that treatment of the effluent with a cation exchange resin (Amberlite(R) IR-120 Plus) was partially effective at reducing, but not removing, toxicity. Phase II characterization tests re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Dorn and Rodgers [5] and Dorn et al [6] conducted studies that identified calcium as the likely toxicant to mysid shrimp. Douglas et al [7] conducted a toxicity identification evaluation (TIE) of an effluent from a petrochemical plant discharging to an estuary. They concluded that toxicity to mysid shrimp was due primarily to an excess of calcium and, to a lesser degree, a deficiency of potassium, magnesium, and bromide.…”
Section: Introductionmentioning
confidence: 99%
“…Dorn and Rodgers [5] and Dorn et al [6] conducted studies that identified calcium as the likely toxicant to mysid shrimp. Douglas et al [7] conducted a toxicity identification evaluation (TIE) of an effluent from a petrochemical plant discharging to an estuary. They concluded that toxicity to mysid shrimp was due primarily to an excess of calcium and, to a lesser degree, a deficiency of potassium, magnesium, and bromide.…”
Section: Introductionmentioning
confidence: 99%
“…Many toxicity identification evaluation manipulations do not remove common ion toxicity and interpretation of test results can be confounded by the presence of other toxicants. In addition, the toxicity identification evaluation manipulations themselves (e.g., cation exchange) can alter ion concentrations and cause toxicity [15]. To aid in the identification of ion toxicity in freshwater, Mount et al [8] conducted more than 2,000 tests with freshwater test organisms to quantify the response to seven common ions.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of KCl was increased and the concentration of NaBr was decreased to maintain K ϩ and Br Ϫ at the same molarity as in [17]. change) can alter ion concentrations and cause toxicity [15].…”
Section: Introductionmentioning
confidence: 99%
“…The potential toxicity of TDS, or specific constituents of TDS, has been well-studied (Horner et al, 2011;Soucek, 2007;Soucek et al, 2011;Brix, Gerdes, Curry, Kasper, and Grosell, 2010;Kennedy et al, 2003;Murray-Guide et al, 2003;LeBlond and Duffy, 2001). Total dissolved solids may induce toxicity to aquatic organisms by exerting general osmotic stress or by a variety of alternative mechanisms associated with specific constituents or the combinations (ion ratios) of the specific components of the TDS (Grosell et al, 2007;Douglas et al 1996). In some cases, general osmotic stress and highly specific mechanisms act in an interactive manner.…”
Section: Discussionmentioning
confidence: 99%
“…More recent attention has been placed on inorganic contaminants, including specific ionic fractions that comprise the TDS (Soucek, 2007;Soucek et al, 2011;Brix, Gerdes, Curry, Kasper, and Grosell, 2010;. For the benthic macroinvertebrate species, including Daphnia magna and D. pulex with simplistic osmoregulation processes (Grosell et al, 2007;Morris, 2001;Schoffeniels, 1976), speciflc fraction of TDS and ionic imbalances in water have been recently shown to be a significant toxicity risk (Kennedy et al, 2005;Douglas et al, 1996).…”
Section: Introductionmentioning
confidence: 99%